ANALYSIS OF ICE FACTORY PRODUCTION IN TECHNICAL IMPLEMENTING UNIT (UPT) DUMAI CITY, RIAU PROVINCE - M. Elvan Ihza Rasyid; Polaris Nasution; Syaifuddin Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT The Technical Implementation Unit (UPT) in Dumai City is the only fishing port managed directly by the Riau Provincial Government, previously managed by the Dumai City Government. Fishermen who moor their boats at UPT Dumai City come from Dumai City and its surroundings, such as Rupat Island, and some fishermen who come from Sinaboi (Rokan Hilir) . The purpose of this study is to analyze the demand, need, and availability of ice blocks produced at UPT Dumai Fishery Port. This research was conducted in January 2020. Located at the Technical Implementation Unit (UPT) of the Dumai Fishery Port, Dumai City, Riau Province . The method used in this research is a survey method, namely by conducting direct observations, interviews and calculations. Data regarding the availability of ice-making materials, the amount of material spent in one production, the amount produced in one day and the capacity of the ice machine at the UPT Dumai Fishery Port . The total production cost in 2019 is Rp. 668,351,530 sourced from the 2019 APBD, with a basic cost of Rp. 6,423,200 in one production, including raw materials, sales and maintenance. The use of non- Iodium salt as a staple in one production is 15-17 sacks, and the weight of 1 sack of salt is 50 kg, with the brand spinning wheel. The price for 1 kg of salt with a standard price of Rp. 6,500 / kg. To reach the Breakeven Point of Production (TIP), the total number of ice blocks produced in a year is 50,400 sticks, with an income of Rp. 1,260,000,000 per year. Meanwhile, ice block production in 2 019 was 18,771 sticks, with an income of Rp. 469,275,000. N use values Overall Equipment Effectiveness (OEE) which obtained 13% , has not been effective at the standard OEE 85% .Keywords : Ice Block, OEE, Port, Salt